The Equidae from Gladysvale, a Hominin locality in the Cradle of Humankind, South Africa - Van der Merwe, Daniel Jean (University of the Witwatersrand, Johannesburg, 2023)
The later Pleistocene compared to modern census data indicated that Equidae are represented lower than comparably sized bovids (BOV III & IV). The reason for this may be due to numerous factors that have been previously investigated such as, landscape usage, carnivore and prey relationships and accumulation factors. However, a largely unexplored factor that may also have played a vital role in their lower representation may have been the difference and effectiveness of predator avoidance behaviours utilized by Equidae. The Equidae remains from the external and internal deposits of Gladysvale (730 to 580 Kya and 257 to 195 Kya) in the Cradle of Humankind, may provide insight into the predatory avoidance behaviours of two different Equidae species, Equus capensis and Equus quagga. This study aimed to create and renew an understanding of the role of these animals within larger faunal communities in the Cradle of Humankind. Equidae fossil material mostly from Gladysvale along with supporting material from Sterkfontein, Kromdraai and Coopers were examined, measured and photographed, in an attempt to broaden the understanding of Equidae relations within the Cradle of Humankind. Furthermore, to also elaborate on the potential differences between Equus capensis and Equus quagga. Past research has usually assigned Equus capensis to the larger version of Equus quagga during the later Pleistocene, with other studies based on DNA analysis suggesting the two species have very little intraspecific diversity. However as seen in this study it would appear that there is a notable difference in size between the two Equidae species, but also a difference in overall representation within the Cradle of Humankind. This could imply that not only are the two species different in size but that they also employed different predatory avoidance behaviours.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science (Evolutionary Studies Institute), Faculty of Science, School of Geosciences, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Cradle of Humankind; Gladysvale; Equidae; Equus capensis; Equus quagga; UCTD; SDG-15: Life on land